2003
DOI: 10.1046/j.1365-2699.2003.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for indigenous selection and distribution of the shea tree, Vitellaria paradoxa, and its potential significance to prevailing parkland savanna tree patterns in sub‐Saharan Africa north of the equator

Abstract: Aim Woody vegetation patterns in African savannas north of the equator are closely connected to human presence, but the distinctions between natural and anthropogenic landscapes have not been clear to many observers. Criteria for identifying savanna landscapes on a continuum of intensity of anthropic impact are explored.Methods A key savanna tree species, Vitellaria paradoxa (Sapotaceae), was used as model for evaluating anthropic impact. Fruits harvested from tree populations across the species range were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 23 publications
7
128
1
7
Order By: Relevance
“…Its status of being a socially and economically important species may also explain the high RAPD variability within populations. Protection afforded to shea trees during traditional long-term management in parklands (from fire, competition, etc) would be expected to allow diversity to increase, particularly if coupled with amplified gene flow by transportation of fruits from village to village by humans or other animals such as elephants, birds, bats or primates (Lovett and Haq, 2000b;Maranz and Wiesman, 2003). Although cases of deliberate human planting are rare and seeds of the Shea tree are recalcitrant, as they do not maintain their viability during long transportation, models of population genetics have shown that a small number of seeds could be sufficient to reduce genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its status of being a socially and economically important species may also explain the high RAPD variability within populations. Protection afforded to shea trees during traditional long-term management in parklands (from fire, competition, etc) would be expected to allow diversity to increase, particularly if coupled with amplified gene flow by transportation of fruits from village to village by humans or other animals such as elephants, birds, bats or primates (Lovett and Haq, 2000b;Maranz and Wiesman, 2003). Although cases of deliberate human planting are rare and seeds of the Shea tree are recalcitrant, as they do not maintain their viability during long transportation, models of population genetics have shown that a small number of seeds could be sufficient to reduce genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…'Unconscious selection' of superior landraces (high yields, early abscission, improved fruit palatability, etc) has been proposed during the cyclical farm-fallow system when unwanted individual shea trees are removed and intensive fruit harvesting occurs during annual crop cultivation periods (Lovett, 2000). According to Maranz and Wiesman (2003), other more active selection mechanisms are possible and they suggest that the prevalence of V. paradoxa north of the equator indicates pronounced and long-term human involvement in tree dispersal. They have compared the presentday distribution with historical range limits from 200-year-old records and demonstrate that range expansion by human migration has occurred.…”
Section: Marker Distribution and Historical Factorsmentioning
confidence: 99%
“…People, cattle, bats, birds and other animals disseminate the seeds [5], however, the trees are not traditionally planted in a domesticated manner [4,5,8,9], but rather the decision to keep or to cut naturally regenerating saplings as a component of an agroforestry system, means the trees are selectively managed, with the result that semi-domestication is potentially occurring through the process that [9] describes as automatic or unconscious selection. Many indigenous agricultural annual and perennial crops have been domesticated, are still cultivated and continue to be traded in large volumes across West-Central Africa, a region that [10] refers to as part of a vast sub-Saharan "noncenter" of agricultural origin.…”
Section: Shea Tree As a Traditional Crop And Domestic Commoditymentioning
confidence: 99%
“…Many indigenous agricultural annual and perennial crops have been domesticated, are still cultivated and continue to be traded in large volumes across West-Central Africa, a region that [10] refers to as part of a vast sub-Saharan "noncenter" of agricultural origin. Across West Africa, it has been noted that this process has resulted in an increasing density of desirable traits in shea trees maintained in parklands as opposed to natural woodland formations, e.g., fruit yield, sweetness and fat content [7,8,11].…”
Section: Shea Tree As a Traditional Crop And Domestic Commoditymentioning
confidence: 99%
See 1 more Smart Citation